Hepatic saturated fatty acid fraction is associated with de novo lipogenesis and hepatic insulin resistance - Kay H. M. Roumans (Nature Portfolio, 2020)
Hepatic steatosis is associated with poor cardiometabolic health, with de novo lipogenesis (DNL) contributing to hepatic steatosis and subsequent insulin resistance. Here, the authors use 1H-MRS methodology to show hepatic SFA fraction is a measure of DNL and specifically may hamper hepatic insulin sensitivity.